Confronting the palm oil crisis: Identifying behaviours for targeted interventions. Issue 103 (January 2020) - Sundaraja, Cassandra Shruti; Hine, Donald W.; Lykins, Amy
Highlights: Purchasing products with sustainable palm oil is a beneficial target behavior. Encouraging manufacturers to use sustainable palm oil might have the highest impact. Awareness and concern about palm oil predicted 33% variance in penetration. Awareness and concern about palm oil predicted 46% variance in probability. Abstract: Palm oil is an edible oil with a high yield, various economic benefits, and many diverse uses. However, its production has led to increased deforestation, the endangerment of several species, and toxic greenhouse gas emissions. The current study had two aims: (1) to generate a list of palm oil-related pro-environmental behaviours (PEB) that general community members in Australia can do; and (2) to identify one or more behaviours from this list to address in a behaviour-change intervention. Semi-structured interviews with 12 experts (environmental journalists, conservation scientists and activists) generated a list of 11 potential palm oil-related PEB. The same experts rated this list in terms of potential effectiveness in reducing the negative environmental effects of palm oil. A community sample of 300 participants rated the same PEB on likelihood of adoption and current penetration (i.e., the extent to which they already engage in the behaviour). These scores were integrated into a behaviour prioritization matrix, which revealed that the most beneficial PEB to target was "purchasing products containing only sustainable palm oil". This study is an essential preliminary step in behaviour change interventional research, and outlines the process of selecting specific consumer behaviour related to environmental concerns. Policy-based implications are discussed.